2020
DOI: 10.1039/d0ce00241k
|View full text |Cite
|
Sign up to set email alerts
|

Anion templated crystal engineering of halogen bonding tripodal tris(halopyridinium) compounds

Abstract: Crystal engineering of halogen bonding tripodal receptors is found to be highly dependent on solvent and choice of anion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 47 publications
4
23
3
Order By: Relevance
“…As shown in Figure 2, the iodine atoms of the TTF are engaged in directional interactions with the chloride anion (ffCÀ I•••Cl À = 174-175°), with I•••Cl À distances (2.96-2.97 Å) much shorter than the contact distance (3.79 Å) determined as the sum of iodine van der Waals radius (1.98 Å) and chloride ionic radius (1.81 Å), giving a reduction ratio (RR) well below 0.8 (0.78). This represents one of the shortest I•••Cl À XB interaction reported so far [16,17] and the shortest one involving iodinated TTFs. The chloride is interacting with two iodine atoms giving then a kind of μ 2 "coordination" around the halide.…”
Section: Structural Properties: Intermolecular Interactionsmentioning
confidence: 68%
“…As shown in Figure 2, the iodine atoms of the TTF are engaged in directional interactions with the chloride anion (ffCÀ I•••Cl À = 174-175°), with I•••Cl À distances (2.96-2.97 Å) much shorter than the contact distance (3.79 Å) determined as the sum of iodine van der Waals radius (1.98 Å) and chloride ionic radius (1.81 Å), giving a reduction ratio (RR) well below 0.8 (0.78). This represents one of the shortest I•••Cl À XB interaction reported so far [16,17] and the shortest one involving iodinated TTFs. The chloride is interacting with two iodine atoms giving then a kind of μ 2 "coordination" around the halide.…”
Section: Structural Properties: Intermolecular Interactionsmentioning
confidence: 68%
“…As chloride anions are potentially coordinating and may interfere with the self-assembly process, we exchanged these for non-coordinating BPh 4 -anions in quantitative yield. We attempted to prepare 2 31 in an analogous manner using a Suzuki coupling of tris-bromomethyl compound 5 [36] and 4-cyanophenylboronic acid in conditions similar to those reported by Kotha et al [37] We were able to prepare the new tris-nitrile 6, albeit in relatively low yield (27 %). However, attempts to convert this into the tris-amidinium 2 31 were unsuccessful with a mixture of products being observed: mass spectrometry and NMR spectroscopy indicated that some product was formed but we were not able to isolate this or drive the reaction to completion.…”
Section: Synthesis Of Tectonsmentioning
confidence: 89%
“…The tetraphenyl tris-alkyne 3, [35] the tris(hexyloxy)benzene trisbromomethyl compound 5, [36] bis-amidinium 8 . (BPh 4 ) 2 , [28] TBA 2 .…”
Section: General Remarksmentioning
confidence: 99%
“…We attempted to prepare 2 3+ in an analogous manner using a Suzuki coupling of tris-bromomethyl compound 5 35 and 4-cyanophenylboronic acid in conditions similar to those reported by Kotha. 36 We were able to prepare the new tris-nitrile 6, albeit in relatively low yield (27%).…”
Section: Synthesis Of Tectonsmentioning
confidence: 99%
“…The tetraphenyl tris-alkyne 3, 34 the tris(hexyloxy)benzene tris-bromomethyl compound 5, 35 bis-amidinium 8•(BPh4)2, 28 TBA2•TP, 40 and TBA2•IP 28 were prepared as previously described. Dry THF was distilled from sodium prior to use, other chemicals were brought from commercial suppliers and used as received.…”
Section: Experimental General Remarksmentioning
confidence: 99%